2008
DOI: 10.1007/s10570-008-9228-2
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of anodic photocurrent generation systems by use of 6-O-dihydrophytylcellulose as a matrix or a scaffold of porphyrins

Abstract: Langmuir-Blodgett (LB) films containing porphyrin molecules were fabricated by use of 6-Odihydrophytylcellulose (DHPC) toward anodic photocurrent generation systems. To suppress the porphyrin aggregation, two different approaches were applied: (1) mixing a low-molecular-weight porphyrin having a diterpenoid carbon skeleton (DPor) with DHPC as a matrix (matrix fabrication) and (2) bonding porphyrin molecules to the hydroxyl groups of DHPC covalently, converting into 6-O-dihydrophytyl-2,3-di-O-[p-(10,15,20-triph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In this case the efficiency was slightly lower than with carbazole, most likely because porphyrins are bulkier and can also interact with each other at a distance of two glucosidic units. Similarly to carbazole, porphyrin was better dispersed when it was regioselectively bonded to cellulose at the C6 instead of the C2–C3 position . In addition, evidence of the templating effect of cellulose to drive porphyrin organization into a helical chiral form came from the intense bisignate Cotton effect ( λ max = 424 nm) of 2,3‐ O ‐methyl‐6‐ O ‐porphyrinylcellulose, its negative sign indicating a left‐handed helical conformation.…”
Section: Bio‐related Polymers With Covalently Bound Organic Chromophoresmentioning
confidence: 99%
“…In this case the efficiency was slightly lower than with carbazole, most likely because porphyrins are bulkier and can also interact with each other at a distance of two glucosidic units. Similarly to carbazole, porphyrin was better dispersed when it was regioselectively bonded to cellulose at the C6 instead of the C2–C3 position . In addition, evidence of the templating effect of cellulose to drive porphyrin organization into a helical chiral form came from the intense bisignate Cotton effect ( λ max = 424 nm) of 2,3‐ O ‐methyl‐6‐ O ‐porphyrinylcellulose, its negative sign indicating a left‐handed helical conformation.…”
Section: Bio‐related Polymers With Covalently Bound Organic Chromophoresmentioning
confidence: 99%
“…Langmuir-Blodgett films of porphyrin-cellulose show improved photocurrent generation in electrochemical cells compared to porphyrin films, indicating the beneficial role of cellulose as a scaffold (Sakakibara, Ogawa, & Nakatsubo, 2007). The chromophores are spaced at a fixed distance using cellulose with its rigid structure and thus the photocurrent quantum yields for the LB films are increased (Sakakibara & Nakatsubo, 2008b). A further improvement of photocurrent performance was obtained by the incorporation of fullerene (C60) in porphyrin-cellulose films (Sakakibara & Nakatsubo, 2008a).…”
Section: Fluorescence Of Polysaccharides and Polysaccharide Derivativesmentioning
confidence: 99%
“…Cellulose unique structure, a linear homopolymer consisting of regio‐ and stereo‐specific β‐1,4‐glycosidic linked D ‐glucose units, attracts a great deal of interest for creating advanced materials because of its stiffness, shape‐stable structure, hydrophilicity, stereoregularity, chirality, multifunctionality, and the ability to form supramolecular structures. So far, we have reported on some cellulose Langmuir‐Blodgett (LB) films with the function of photocurrent generation and revealed that introducing porphyrin moiety to the cellulose scaffold has an impact on the magnitude on the anodic photocurrent because of the inhibition of the aggregation of the chromophores (porphyrins) 4, 5. Especially, a regioselectively substituted cellulose derivative having both a porphyrin moiety and stearoyl groups at the C‐6 and C‐2, 3 positions (H 2 PCS) could be one of the promising candidates for well‐defined molecular assembly and highly efficient cellulosic solar cells (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…So far, we have reported on some cellulose Langmuir-Blodgett (LB) films with the function of photocurrent generation and revealed that introducing porphyrin moiety to the cellulose scaffold has an impact on the magnitude on the anodic photocurrent because of the inhibition of the aggregation of the chromophores (porphyrins). [4,5] Especially, a regioselectively substituted cellulose derivative having both a porphyrin moiety and stearoyl groups at the C-6 and C-2, 3 positions (H 2 PCS) could be one of the promising candidates for well-defined molecular assembly and highly efficient cellulosic solar cells (Figure 1). [5] The structure of H 2 PCS was designed on the basis of our fundamental concept, role-sharing functionalization of cellulose; to impose precise function for each hydroxyl group of repeating cellulose unit.…”
mentioning
confidence: 99%